The Role of Governance Mechanisms in Improving the Performance of Economic Entities - Al-Shammari, Suaad Adnan Noaman; Al-Anbagi, Ahmed Taher Kadhim; Ahmed, Wasan Yahia (International Journal of Psychosocial Rehabilitation, 2020)
- The present research aims to review the legal and regulatory frameworks related to governance and compare them with the way local economic units are manage. The deficiencies are then identify and should be consider arriving at a set of conclusions and recommendations that seek to improve the performance of these units. The research problem is a key question, to what extent the application of governance mechanisms contributes to protecting shareholders from conflicts of interest, It is the misconduct of the Unit's officials, the owners of the majority of the shares, As well as enhancing the delivery of information to owners regarding decisions affecting their investments. In order to achieve the objective of the research, descriptive analysis and quantitative analysis were use. In the quantitative analysis, the application of data through a questionnaire was use as a research tool and the Statistical Package for Social Sciences (SPSS) was use to analyze the research data and to reach the results. The most important conclusions were deficiencies in the legal and regulatory environment related to the legislation, laws and instructions of the units, especially with regard to the application of governance and its mechanisms. The most important recommendations were the need to issue a guide for the governance of local economic units as practiced in the rest of the world and to benefit from their experiences in this regard. In particular, the experiences of Arab countries and the attempt to unify the accounting policies followed in the Iraqi units in order to facilitate the task of applying governance on the o ne hand and keep abreast of global and international developments in this regard on the other.